Development of an automatics parallel parking system for nonholonomic mobile robot - Mohd Fairuz , Abdollah; Syed Najib , Syed Salim; Irma Wani , Jamaludin; Muhammad Nizam , Kamarudin (2011)
This paper depicts the development of backward automatic parallel parking system for nonholonomic mobile robot. The configuration of the system consists of ultrasonic sensor, rotary encoder, controller, and actuators. The path planning algorithm is developed based on the data acquired from the sensor. The proposed idea of the path planning is based on the geometrical equations in which the needed information is referring to the distance between the mobile robot and the adjacent object. The ultrasonic sensor and rotary encoder respectively used to detect parking area and measure the detected space. A PIC32MX360F512L microcontroller is used in order to generate the algorithm and control the movement of the mobile robot. System implementation is briefly described to depict the system as a whole. Experimental results are presented to demonstrate and validate effectiveness of the technique used.